Relación entre fluorosis dental y concentraciones de flúor en orina en estudiantes de 7 a 17 años de edad del colegio san miguel vereda el juncal municipio de Palermo Huila (2017)
The importance of fluoride is very notable when evaluating the reduction of dental caries. At a global level, different countries have reduced this index as a consequence of the incorporation of fluorides in the sources of drinking water, salt, milk and toothpastes, therefore the WHO stipulated that for the prevention of dental caries, the Public Health Service (PHS ) has recommended, since 1962, that public water supplies contain fluoride at concentrations between 0.7 and 1.2 mg/L1. Many studies confirm the importance of fluoride in the prevention of cavities and its role in promoting oral health for more than 50 years.